[Gold, gold and more gold ; Return to Ormoc ; A lasting image [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Tackles Marcos legendary loot, the mansion revealing priceless antiques and art pieces. Features Ormoc City after the flood disaster and its cause. Interview with the photographers of Mt. Pinatubo with their coffee table book project.